Social and Environmental Accounting for Sustainable Development and Potential Research in Vietnam - Nguyen, Thi Phuong Dung; Nghiem, Ngoc Anh (JST: Engineering And Technology For Sustainable Development, 2024)
With the increasing adoption and usage of social and environmental accounting, sustainable development has become the goal and priority of countries and organizations. In this global trend, Vietnam has already integrated 17 Sustainable Development Goals (SDGs) of the United Nations with 115 targets into its sustainable national development strategy. Social and Environmental Accounting (SEA) is vital to help governments and organizations achieve sustainable practices journeys. However, SEA is still new for most enterprises in Vietnam. Therefore, this paper reviewed the literature on SEA to identify its characteristics and potential for future research in Vietnam. We employed desk research and systematic literature reviews as research methods. We found a big gap in Vietnamese language-published articles on SEA and international publications. We summarized SEA literature in other countries and Vietnam to see the characteristics of SEA and realized that the number of articles on SEA is still limited in Vietnam. Hence, we proposed the research potentials of SEA in the Vietnamese context for sustainable development, emphasizing the potential impact of this research on the future of sustainable development in Vietnam. Our paper sheds light on a new accounting tool for researchers and practitioners to expand their research and business toward the goal of sustainable development in Vietnam.